Expanded Graphite-Based Materials for Supercapacitors: A Review - Dan Zhang; Chao Tan; Weizhuo Zhang; Weijie Pan; Qi Wang; Le Li (Molecules, 2022)
Supercapacitors have gained e wide attention because of high power density, fast charging and discharging, as well as good cycle performance. Recently, expanded graphite (EG) has been widely investigated as an effective electrode material for supercapacitors owing to its excellent physical, chemical, electrical, and mechanical properties. Based on charge storage mechanism, supercapacitors have been divided into symmetric, asymmetric, and hybrid supercapacitors. Here, we review the study progress of EG-based materials to be electrode materials. Furthermore, we discuss the application prospects and challenges of EG-based materials in supercapacitors.